Cataveiro : Book Two of the Osiris Project - Swift, E. J. (Emma J.) (London Del Rey, 2014)
For political exile Taeo Ybanez, this could be his ticket home. Relations between Antarcticans and Patagonians are worse than ever, and to be caught on the wrong side could prove deadly. For pilot and cartographer Ramona Callejas, the presence of the mysterious stranger is one more thing in the way of her saving her mother from a deadly disease
Keywords: Imaginary wars and battles -- Life on other planets